2′/3′ Regioselectivity of Enzyme‐Free Copying of RNA Detected by NMR. (4th March 2020) - Motsch, Sebastian; Pfeffer, Daniel; Richert, Clemens
Abstract: The RNA‐templated extension of oligoribonucleotides by nucleotides produces either a 3′, 5′ or a 2′, 5′‐phosphodiester. Nature controls the regioselectivity during RNA chain growth with polymerases, but enzyme‐free versions of genetic copying have modest specificity. Thus far, enzymatic degradation of products, combined with chromatography or electrophoresis, has been the preferred mode of detecting 2′, 5′‐diesters produced in enzyme‐free reactions. This approach hinges on the substrate specificity of nucleases, and is not suitable for in situ monitoring. Here we report how 1 H NMR spectroscopy can be used to detect the extension of self‐templating RNA hairpins and that this reveals the regioisomeric nature of the newly formed phosphodiesters. We studied several modes of activating nucleotides, including imidazolides, a pyridinium phosphate, an active ester, and in situ activation with carbodiimide and organocatalyst. Conversion into the desired extension product ranged from 20 to 90 %, depending on the leaving group. Integration of the resonances of H1′ protons of riboses and H5 protons of pyrimidines gave regioselectivities ranging from 40:60 to 85:15 (3′, 5′ to 2′, 5′ diester), but no simple correlation between 3′, 5′ selectivity and yield. Our results show how monitoring with a high‐resolution technique sheds a new light on a process that may have played an important role during the emergence of life. Abstract : Prebiotic chemistry : Extension of an RNA primer can produce 2′‐5′ and 2′‐5′ phosphodiesters. In situ monitoring by NMR spectroscopy provides an unbiased view of the regioselectivity of this reaction and demonstrates how strongly template and leaving group favor the natural isomer.